Pro-Kontra Perspektif Ulama Terhadap Penginvestasian Dana Zakat: studi pendapat ulama - Fauzan, Faisal (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2020)
The purpose of this study is to describe these two opinions and the points of their study of the final legal status of investment activities using zakat funds. As a type of library research, this research uses the literature data which concluded two perspectives of ulama that allow and reject investment by using funds from zakat. Results reveal considerations of the view that permits the investment of zakat funds is to take hadith values from Zaid bin Aslam, namely the practice of Rasulullah SAW and Caliph Umar Bin Khattab who made use of the zakat wealth before it was delivered to his mustahik. This opinion also paid attention to the ijtihad or law policy of the caliph Umar bin Khattab who sought the property of orphans, stopped paying zakat for muallaf, and replaced fa'i for the soldiers by giving monthly salaries from Baitul Maal. Opinions that do not allow the investment of zakat funds stand on a hadith from Aisha RA,